Integrating surface and subsurface influences to assess groundwater potential in a rapidly urbanizing temperate region: A Geographic Information System-Analytical Hierarchy Process (GIS-AHP) case study of Shelby County, Tennessee - Tareq Jamal Chy; Khairul Hasan; Asif Bin Alam Seum; Khayrun Nahar Mitu (Green Technologies and Sustainability)
The overutilization of groundwater and the significant weather transformations over the years have placed immense strain on global groundwater reserves. As the demand for potable water across the world for human consumption, agricultural, and industrial use grows, so does the necessity to assess the groundwater potential and productivity of aquifers. In recent years, geographic information system based studies have become increasingly prominent in groundwater exploration due to its promptness and the direct data it provides on the resource for further development. Therefore, the present study was conducted with the objective of demarcating the groundwater potential zone of Shelby County, Tennessee. To this end, Geographic Information System (GIS) and Analytical Hierarchical Process (AHP) techniques were employed to create 8 thematic layers, such as elevation, slope, drainage density, lineament density, rainfall, land cover, soil group, and porosity. Weights allocated to the various classes of the thematic maps were based upon insight via the AHP method. The exploration of Shelby County’s groundwater revealed a stratification of five distinct potentials – very low, low, moderate, high, and very high – with the moderate zone occupying the greatest portion at 62.5%. The low and high zones followed at 8.92% and 28%, respectively, and the very low and very high potentials were only observed in tiny, isolated sections. These findings can grant policymakers the insight needed to make prudent, sustainable decisions in regards to the management of the study area’s groundwater resources.